Effects of propolis on blood lipid and liver lipid of hyperlipidemic SD rats - HU Fu-liang; ZHAN Yao-feng; CHEN Min-li; YING Hua-zhong; ZHU Wei (浙江大学学报. 农业与生命科学版)
Effects of proplis extracted by water and by ethanol on blood lipid and liver lipid of hyperlipidemic Sprague Dawley (SD) rats were studied. The results showed that either of the extracted propolis had significant inhibitory effect on the level of triglyceride (TG), total cholesterol (TC), LDL-C, GPT and GOT in serum, and TC, TG and MDA in liver, but were ineffective on HDL-C, MDA, SOD and NO levels in serum. Ethanol extracted propolis also reduced the body weight, liver weight and liver index of hyperlipidemic SD rats, while water extracted propolis were adiaphorous. Thus the two extracts are believed to be helpful in improving lipid metabolization of hyperlipidemic SD rats and provided with antioxidant activity.